An Effective Gender-Affirming Care and Hormone Prescribing Standardized Patient Case for Residents - Ben J. Hersh; Rebecca E. Rdesinski; Christina Milano; Rebecca E. Cantone (Association of American Medical Colleges, 2022)
Introduction It is estimated that at least 700,000 individuals in the United States identify as transgender or gender expansive. Many have confronted marginalization within the health care system, leading to suboptimal care and inequitable health outcomes. Health sciences trainees do not receive adequate training in gender-affirming care. The authors therefore created, piloted, and evaluated a formative standardized patient case for gender-affirming care for family medicine resident learners that could be given with limited resources in primary care and health professional education. Methods The curriculum for the case was developed with patient input and with family medicine physicians skilled in education, simulation, and gender-affirming care. The first case was held for 20 residents in a 4-year family medicine program in the Pacific Northwest. Nineteen participants completed pre/post case surveys delineating knowledge, awareness, attitudes, and intended behavior regarding providing gender-affirming care. Results Self-reported knowledge and awareness increased after standardized patient case participation in multiple skill areas related to providing gender-affirming care. Faculty observers informally reported that the session increased their knowledge and comfort as well. Discussion Implementation of this gender-affirming standardized patient case inclusive of community input was associated with successful improvements in self-reported measurements of resident knowledge and awareness of providing gender-affirming care. Additional institutions should consider such training to improve health care equity for this population.